Elaboration of the Method for Safety Assessment of Subsea Pipeline with Longitudinal Buckling - Liudmila Muravyeva; Nikolai Vatin (Advances in Civil Engineering)
The issue of ensuring longitudinal stability of marine gas pipelines has been raised in view of construction of pipelines operating at significant temperature drops. Most commonly the pipelines deviation from the design conditions as well as equilibrium disturbance occurs due to longitudinal buckling. The task of designing the marine gas pipeline involves making the reliability analysis of the pipeline, taking into account the required conditions of structural reliability in all construction phases. As per the Russian standards, the vertical buckling is not considered in the stability analysis, whereas the standards of the USA, Norway (DNV-RP-F110), and the Great Britain emphasize the need for considering the lateral buckling caused by axial forces. This paper focuses on the operational reliability calculation for an underwater main gas pipeline, in which longitudinal buckling failure occurred. The calculation is based on the probabilistic and statistical method of assessing the pipeline state and operational reliability.